KUALITAS PELAYANAN KLINIK KEPEGAWAIAN DI BADAN KEPEGAWAIAN DAERAH KABUPATEN POSO - Furqan, Muh. (Katalogis, 2017)
In Public Service context, nation is a major actor and being the first to be responsible in fulfilling thepeople rights, not others. The same thing happens to the public service submission process,Â the nation plays the important role dominantly. People demand to the government performance in the government event submission dan public service became stronger and undeniable along the existence of politic reformation which has been supporting people to be more critical and more aware of their rights to have a good governance. This research purpose is to know why the Service of Servant Clinic at the Regional Servant Institution (BKD) of Poso Regency did not run well based on the rules. The used method was a qualitative method through the explorative approach. The result showed that from the existence of five dimensions had been fulfilled, however, the Tangibles dimension had not been optimal in giving the service to the servants who used the service of Servant Clinic at the Regional Servant Institution (BKD) of Poso Regency.